왕불류행(王不留行)의 구성 성분 및 생리활성에 대한 문헌 고찰 - 김지우; Ji-woo Kim; 이준; Jun Lee; 이미현; Mee-hyun Lee (大韓本草學會誌, 2025)
Objective : The review aims to comprehensively investigate the phytochemical constituents and pharmacological properties of Melandrium firmum, a plant traditionally used in East Asian medicine. Methods : A systematic literature review was conducted using multiple databases, including RISS, Google Scholar, OASIS, and PubMed. A total of 32 relevant publications were selected and analyzed. We searched for terms related to "Melandrii herba", "M. firmum", including Melandrium firmum. Results : The majority of studies on M. firmum employed extraction solvents such as methanol (MeOH), ethanol (EtOH), and water. A total of 71 phytochemicals have been identified from M. firmum, including notable constituents such as 20-hydroxyecdysone, firmosides A and B. Reported pharmacological effects include antihyperlipidemic and anti-obesity activities, antioxidant and anti-inflammatory effects, cytotoxic and anticancer properties, amelioration of benign prostatic hyperplasia, anti-aging effects on skin, hair-growth promotion, and prevention of osteoporosis. Conclusion : Traditionally known as "Wangbulryuhaeng" in Korean medicine, Melandrii herba has been applied externally for wound healing, hemostasis, and pain relief, and internally for conditions such as breast cancer, lactational disorders, and gonorrhea. This review summarizes the current knowledge on its bioactive compounds and pharmacological potential. Future research should prioritize optimizing extraction and fractionation protocols, selecting appropriate solvents, and using advanced chromatographic and spectrometric techniques to better characterize its therapeutic constituents. In addition, well-designed in vivo and clinical studies are required to validate its traditional uses, corroborate existing pharmacological evidence, and elucidate synergistic mechanisms in combination formulations that have demonstrated superior anti-inflammatory, anticancer, and cytotoxic activities, thereby guiding the development of novel therapeutic agents.